Stock market listing and the use of trade credit: Evidence from public and private firms - Abdulla, Yomna; Dang, Viet Anh; Khurshed, Arif (Journal of Corporate Finance, 2017)
This paper examines differences in the use of trade credit by publicly listed firms and their privately held counterparts. We show that public firms maintain a significantly lower level of trade credit than private firms. This finding is consistent with the argument that public firms rely less on supplier financing because of their greater access to cheaper and less risky sources of external capital. We further find that while public and private firms actively seek to adjust toward their optimal trade credit levels, the former firms experience faster adjustment. The recent financial crisis had differential effects on the trade credit ratios of public and private firms.